Effects of water stress on lavender and sage biomass production, essential oil composition and biocidal properties against Tetranychus urticae (Koch) - Chrysargyris, Antonios; Laoutari, Sotiroula; Litskas, Vassilis; Stavrinides, Menelaos; Tzortzakis, Nikos (My University, 2016)
© 2016 Elsevier B.V.We investigated the effect of water stress on the growth and essential oil quality of lavender (Lavandula angustifolia) and Greek sage (Salvia fruticosa) plants. In addition, we assessed the toxicity of essential oils to females of the two-spotted spider mite (Tetranychus urticae). Lavender and sage plants were grown in a greenhouse under adequate irrigation (AI), moderate (MWD) and severe water deficit (SWD). Plant growth related parameters, total phenols and total chlorophylls content as well as the yield and composition of essential oils hydrodistilled from the plants were assessed. In general, plants under water stress exhibited reduced growth and altered chemical composition than plants under regular irrigation. In addition, water stressed plants benefited in essential oil yield and quality, with higher concentrations of antioxidants (phenolic) level. The LC50 of lavender essential oil vapors from control plants was estimated at 4.93 μl/l, while that of Greek sage at 3.77 μl/l. Essential oil vapors from lavender plants under MWD caused significantly higher mortality to T. urticae females, than essential oils from plants under AI. In contrast, essential oils from sage plants under water stress caused similar mortality to T. urticae irrespectively of water stress levels.
Keywords: Toxicity; GC/MS; Lavandula angustifolia; Salvia fruticosa; Plant stress; Spider mites